The Economic Impact of the Affordable Care Act on Arkansas - Carter C. Price, Evan Saltzman (RAND Corporation, 2013)
The Affordable Care Act is a substantial reform of the health care insurance system in the United States. Its effects will have a significant impact on state and local economies that require detailed analysis. This document assesses the economic effects of the Affordable Care Act on the state of Arkansas. This document is an examination of the economic impact of the Affordable Care Act (ACA) on Arkansas. The ACA will increase coverage through the expansion of Medicaid and the creation of a Health Insurance Exchange with subsidies. We used the RAND COMPARE model to analyze the ACA’s economic impact on Arkansas. We found that by 2016 about 400,000 people will be newly insured, net federal payments to the state will amount to $430 million annually, and the total gross domestic product will be a net increase of $550 million. The research was sponsored by the Arkansas Center for Health Improvement and conducted in RAND Health, a division of the RAND Corporation. A profile of RAND Health, abstracts of its publications, and ordering information can be found at www.rand.org/health. The authors would like to thank Christine Eibner and Chapin White for their thoughtful comments and reviews of this document.